A Confucian Social Model of Political Appointments among Chinese Private-Firm Entrepreneurs - Li, Xu-Hong; Liang, Xiaoya (Academy of Management Journal, 2015)
In China, many successful private-firm entrepreneurs hold representational appointments in political councils such as the People's Congress (PC) or People's Political Consultative Conference (PPCC). By considering Western theories of life career development and Confucian doctrines of personal development, we seek to understand the complex motivations of successful entrepreneurs for joining political councils. We propose a Confucian social model of role transition to explain the pursuit and attainment of political appointment in China. We hypothesize that the “proself” and “prosocial” motives for seeking political connections will, respectively, attenuate or strengthen the relationship between private-firm entrepreneurs' business success and their intention and attainment in seeking political appointment. We conducted a cross-sectional survey of 166 private-firm chief executive officers (CEOs) and chairs, and a longitudinal archival study of 1,323 Chinese publicly listed private firms from 2006 to 2012. The findings support our hypotheses on the moderating effect of the proself and prosocial motives. The study offers insights into how Confucian cultural values may explain the dynamic between business success and political appointments among private-firm entrepreneurs in China.